Martin Luther : renegade and prophet - Roper, Lyndal (New York : Random House, 2017)
"Examining the inner life of Martin Luther, the founding leader of the Reformation, the author reveals a literary genius who was full of contradictions and whose Ninety-Five Theses began the greatest upheaval and transformation of Christianity in history"--NoveList.
Mansfeld and mining -- The scholar -- The monastery -- Wittenberg -- Journeys and disputations -- The Leipzig debate -- The freedom of a Christian -- The Diet of Worms -- In the Wartburg -- Karlstadt and the Christian city of Wittenberg -- The Black Bear Inn -- The Peasants' War -- Marriage and the flesh -- Breakdown -- Augsburg -- Consolidation -- Friends and enemies -- Hatreds -- The charioteer of Israel.
Includes bibliographical references and index.
Keywords: Luther, Martin, -- 1483-1546.; Reformation -- Germany -- Biography; Lutheran Church -- Germany -- Clergy -- Biography; Biographies